Bioprospecting the Cerrado’s Aromatic Flora: Chemical and Biological Studies of Three Essential Oils - Rodrigues,Gardênia Barbosa Carrijo (2023)
Abstract Chemical and pharmacological potentials of botanical species found in the Cerrado are well-known and widely studied. Chemical diversity of secondary metabolites produced by plants that belong to this Brazilian biome has triggered several studies in the fields of farming, pharmaceutical and cosmetic industries. Therefore, this study aimed at evaluating the chemical composition of essential oils (EOs) from fresh leaves of three species found in the Brazilian Cerrado: Cardiopetalum calophyllum Schltdl. (EO-CC), Campomanesia adamantium (Cambess.) O. Berg (EO-CA) and Protium ovatum Engl. (EO-PO) and at determining their anti-Malassezia furfur and anti-inflammatory activities. Both GC-FID and GC-MS showed that the most abundant chemical class of the oils was the one of sesquiterpene hydrocarbons. The major constituents identified in EO-CC were germacrene D (34.9%) and bicyclogermacrene (26.8%). EO-CA exhibited mainly germacrene D (21.7%) while EO-PO had high concentrations of germacrene D (25.0%) and γ-muurolene (18.6%). EOs were tested by the broth microdilution method on 96-well microplates and exhibited satisfactory activity against M. furfur, i. e., EO-CA had MIC = 375 µg/mL while EO-CC and EO-PO had MIC = 750 µg/mL. The chemotaxis model, which was used for evaluating their anti-inflammatory activity, showed that EOs exhibited effective results: C. calophyllum (EO-CC; IC50 = 24.4 µg/mL), C. adamantium (EO-CA; IC50 = 15.7 µg/mL) and P. ovatum (EO-PO; IC50 = 32.5 µg/mL). In short, biological activities of EO-CC, EO-CA and EO-PO, such as anti-Malassezia furfur and anti-inflammatory ones, were investigated and described for the first time.